Models to optimise bioengineering of banana wastes to animal feeds and fertilisers. Issue 2 (22nd May 2018) - Nannyonga, Stella; Fryer, Peter; Robbins, Phillip
Abstract : Microbial growth models are usually employed to describe the growth kinetics of microorganisms under optimised operational conditions. Much time and resources are involved in running central composite or Box–Behnken full factorial designs of the experiment (DoEs) before the optimum conditions are attained. In this study, a Taguchi model (two-level) was used for DoEs and kinetic parameters derived from the mathematical models were used for process optimisation. This resulted in running less 'robust' anaerobic digestion experiments for the varying selected parameters – that is, pH and temperature. Chapman–Richards model results were considered to represent experimental data and were compared with the kinetic parameters derived from the Bergter, Andrews and Contois models. Also, a pure population of Saccharomyces cerevisiae (Saf-instant) was used, unlike in many studies where mixed populations are employed for anaerobic digestion. From the model results, a pH of 4·6–5·6 and a temperature of 25–30°C were considered optimum for S. cerevisiae anaerobic growth on banana waste. Chemical characterisation of the digested banana wastes under optimised conditions indicated an increase in proteins and lipids by 7 and 5%, respectively, and an approximately 8% mineral content increase was also noted. The waste could also be used as a nutrient-rich fertiliser and chicken feed supplement.